2022
DOI: 10.1002/chem.202200458
|View full text |Cite
|
Sign up to set email alerts
|

Design of Stimuli‐Responsive Phenothiazine Derivatives with Triplet‐Related Dual Emission and High‐Contrast Mechanochromism Guided by Polymorph Prediction

Abstract: The development of high‐contrast stimulus‐responsive materials with excited triplet emission is of great significance for anti‐counterfeiting, sensor and memory applications, but remains a challenge. Here, we report a strategy for the rational design of stimulus‐responsive phenothiazine derivatives with triplet‐related dual emissions and high‐contrast mechanochromism guided by Polymorph Prediction. The designed phenothiazine derivatives have the characters of simple structures, a facile synthetic procedure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…quasi-axial and quasi-equatorial, resulting in two distinct CT energies as in phenothiazine ( vide supra ). Such behaviour of the PTZ donor has been widely investigated 47–51 in the past, and we speculate the DDA donor behaves in a similar manner. In this case each of these 1 CT states discussed above is associated with one of the two conformers rather than localized on the same molecule.…”
Section: Resultssupporting
confidence: 55%
“…quasi-axial and quasi-equatorial, resulting in two distinct CT energies as in phenothiazine ( vide supra ). Such behaviour of the PTZ donor has been widely investigated 47–51 in the past, and we speculate the DDA donor behaves in a similar manner. In this case each of these 1 CT states discussed above is associated with one of the two conformers rather than localized on the same molecule.…”
Section: Resultssupporting
confidence: 55%
“…A TPE-dioxaborine fluorophore reported by Yang et al with four polymorphs and one amorphous solid state exhibited four emission colors ranging from green to red . Xiao and Yi et al also designed high-contrast MRL materials by polymorph prediction. , …”
Section: Introductionmentioning
confidence: 99%
“…23 Xiao and Yi et al also designed high-contrast MRL materials by polymorph prediction. 24,25 As the most concerned aggregation-induced emission (AIE) group, TPE has always been favored by researchers because of its unique advantages, and many TPE derivatives were found to be polymorphous. The blue fluorescence of TPE could be easily regulated by introducing strong electron-donating and electronaccepting groups.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we successfully screened out a series of highcontrast mechanochromic molecules by predicting potential polymorphs. 40,41 Due to the fact that sufficient crystal structures have not been obtained to match the predicted ones, the reliability of this strategy needs to be proved. Our previous studies demonstrated that a D-p-A molecule has a higher potential to emit polymorphism-dependent fluorescence.…”
Section: Introductionmentioning
confidence: 99%